Anxiety and Stress among B.Sc. Nursing First Year Students in a Selected Nursing College at Lekhnath, Pokhara, Nepal - Silwal, M; Gurung, R; Gurung, A; Sah, I; Koirala, D; Ojha, S (Journal of Gandaki Medical College-Nepal, 2019)
Background: Nursing students are important human resources in the field of health. Detection of potential anxiety and stress among nursing students is crucial since anxiety and stress can lead to low productivity, low quality of life, and suicidal ideas. Identifying factors affecting anxiety and stress in initial period of college among nursing students can help nursing educators to find ways to decrease anxiety and stress. Objectives: To assess the anxiety and stress among B.Sc. nursing first year students in their initial college life. Methods: A cross-sectional descriptive research design was used for this study. Consecutive sampling technique was used to select the subjects. Total 13 students (100%) were taken as a sample and standardized Beck anxiety scale and modified scale for academic stress was used to collect data. Results: The study shows that majority of the students, 8 (61.5%) were in the age of 18 years old, follows Hindu religion, 10 (76.9%) belonged to upper caste, 11 (84.6%) stayed in urban area, 7 (53.8%) had no difficulty in this college. Out of 13, 2 (15.4%) students had moderate anxiety and 11 (84.60%) had low level of anxiety with 1.15 ±0.37 whereas 6 (46%) students had mild stress and 7 (54%) had moderate level of stress with 1.53 ±0.51. There were no significant association of anxiety score and stress score with age, ethnicity, residence, feeling difficulties in the college with p < 0.05; 6 (46%). There was low positive correlation between anxiety and academic stress with rp = 0.395. It was found that the cause of anxiety was due to college environment, seniors ragging, difficult subjects, delay session and can be reduced by stopping seniors ragging, providing transportation, starting session on time, counselling, providing lunch in canteen, friendly environment, free hours for library. Conclusions: Students who are newly taking admission to nursing profession will have mild form of psychological variation. Students are mainly faced with practical and academic stressors and anxiety. Hence the study strongly suggests that, starting session on time, time management, avoid ragging, student counselling are the most important factors to reduce anxiety and academic stress to the newly admitted students.